2008
DOI: 10.1038/sj.ejhg.5202000
|View full text |Cite
|
Sign up to set email alerts
|

A splice-site mutation and overexpression of MYO6 cause a similar phenotype in two families with autosomal dominant hearing loss

Abstract: Hearing loss is the most common sensory disorder, affecting 1 in 650 newborns. Linkage analysis revealed linkage to locus DFNA22 in two Belgian families 1 and 2 with autosomal dominant sensorineural hearing loss. As MYO6 has previously been reported as responsible for the hearing loss at loci DFNA22 and DFNB37, respectively, DNA sequencing of the coding region and the promoter of MYO6 was performed but this analysis did not reveal any mutations. However, only in patients of family 2, an insertion of 108 bp was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 25 publications
(21 reference statements)
3
38
0
Order By: Relevance
“…The missense mutation was ruled out by segregation analysis; however, the 4-bp deletion (c.862_865delACAA, p.D288DfsX17) segregated with the phenotype and was not found in 135 ethnically matched controls (270 chromosomes). Because the DFNA22 locus is not represented on AudioGene, phenotypic filtering was not applied; however, the phenotype was consistent with reported DFNA22 audioprofiles (22). Sample 8 carried two candidate variants-one mutation was ruled out by segregation analysis and the other is a known ADNSHL mutation [(DFNA2) c.842C > T, p.L281S] in KCNQ4 (18).…”
Section: Resultsmentioning
confidence: 99%
“…The missense mutation was ruled out by segregation analysis; however, the 4-bp deletion (c.862_865delACAA, p.D288DfsX17) segregated with the phenotype and was not found in 135 ethnically matched controls (270 chromosomes). Because the DFNA22 locus is not represented on AudioGene, phenotypic filtering was not applied; however, the phenotype was consistent with reported DFNA22 audioprofiles (22). Sample 8 carried two candidate variants-one mutation was ruled out by segregation analysis and the other is a known ADNSHL mutation [(DFNA2) c.842C > T, p.L281S] in KCNQ4 (18).…”
Section: Resultsmentioning
confidence: 99%
“…A possible alternative explanation is that there is a regulatory sequence mutation or a position effect mutation in rsv mutant mice that affects Myo6 expression. Two reports have suggested that mutations in regulatory sequences or position effect mutations of Myo6 in the Myo6 sv allele [5] and in a family affected by autosomal dominant deafness [18]. A possible regulatory region of Myo6 was found in mice harbouring a Bmp5 se Myo6 sv allele, which shows stereocilia fusion due to a paracentric inversion caused by a break 30-220 kb upstream of Myo6 [5].…”
Section: Discussionmentioning
confidence: 99%
“…A possible regulatory region of Myo6 was found in mice harbouring a Bmp5 se Myo6 sv allele, which shows stereocilia fusion due to a paracentric inversion caused by a break 30-220 kb upstream of Myo6 [5]. Recently, it was shown by quantitative realtime PCR that mRNA expression of MYO6 in humans is elevated 1.5-to 1.8-fold in family members suffering inherited deafness compared with unaffected family members [18]. No causative mutation was found by genomic sequencing in coding exons, non-coding exons, exon-intron boundaries, UTRs, and the promoter region of MYO6 in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…As might be expected, the human disorders that are associated with these gene disruptions are nonlethal, often are late-onset, and are associated with relatively mild or variable phenotypes that might easily go undetected. The five genes, and their associated diseases, are CEL (maturity-onset diabetes of the young; OMIM: 609812) (Raeder et al 2006), IRAK3 (early onset asthma; OMIM: 611064) (Balaci et al 2007), KRT14 (ectodermal dysplasia syndromes; OMIM: 161000 and 125595) (Lugassy et al 2006), MYO6 (progressive hearing loss; OMIM: 606346) (Sanggaard et al 2008;Hilgert et al 2008), and RP1 (retinitis pigmentosa; OMIM: 180100) (Supplemental Table 6; Guillonneau et al 1999;Pierce et al 1999;Sullivan et al 1999). Three additional human genes with disruptive INDELs have mouse orthologs that are being used as human disease models in the hemizygous state.…”
Section: Coding Indels That Are Likely To Cause Human Phenotypesmentioning
confidence: 99%